The aesthetics of speedrunning: Performances in neo-baroque space - Reed, Emilie (Replay. The Polish Journal of Game Studies, 2022)
Speedrunning describes activities related to the development and performance of strategies to complete games quickly, and is a valuable source of historical and technical information, while producing specialized aesthetic explorations of a videogame’s environment. Most research on speedrunning emphasizes its metagaming or documentary function. However, speedrunning also changes the aesthetic experience of gameplay, both for players and in spectated performance. Aesthetic investigation informed by art historical perspectives, such as Angela Ndalianis’ theory of the Neo-Baroque and H.S. Becker’s study of Art World formations, offers new insights into the experience of speedrunning and how discontinuous and disjointed simulated space is experienced and appreciated as aesthetic phenomena by players and spectators. While Nidalianis has applied her theory to videogames, among other types of contemporary entertainment, further investigating speedrunning performances through this lens extends her analysis and problematizes the idea of a videogame as a singular aesthetic work, instead drawing attention to alternative aesthetic experiences videogames can offer.